Exploring a public interest definition of corruption: public private partnerships in socialist Asia - Gillespie, John (Journal of business ethics, 2020)
As conventionally understood, corruption relies on a set of universally agreed rules that determine what constitutes the appropriate allocation of organizational resources. This article explores whether rule-based approaches to corruption are applicable where business organizations, such as public private partnerships (PPPs), and the public fundamentally disagree about what constitutes an appropriate allocation of resources. Drawing on empirical research about PPPs in Vietnam, this article compares how government, business organizations, and the public conceptualize the transfer of public assets into private ownership. It argues that a public interest approach to corruption is needed where PPPs privatize public assets within the law, but against the express wishes of the public.